Analisis Penggunaan Media Youtube Pada Pembelajaran Menulis Teks Cerita Fabel Siswa Kelas VII SMPN 2 Pebayuran - Jaelani, Jaelani; Rosalina, Sinta; Triyadi, Slamet (Jurnal Ilmiah Wahana Pendidikan, 2024)
Study The use of YouTube media in fable learning aims to make it easier for students during the learning process. This research uses a qualitative approach with descriptive methods. Data collection techniques in this research are observation, documentation and interview techniques. Qualitative data analysis techniques consist of data reduction, data presentation, and drawing conclusions. The research results show that the use of YouTube media as a teaching medium creates conditions and atmosphere in the learning process that are more interesting, less monotonous, and foster enthusiasm so that students do not feel bored during learning. The effectiveness of the successful use of YouTube media is proven by the students' writing which the researcher analyzes is structurally appropriate. These findings prove that YouTube is worthy of being applied in learning fable texts.